Enhancing the shelf stability of fresh‐cut potatoes via chemical and nonthermal treatments. Issue 6 (17th May 2021) - Rashid, Muhammad Hamdan; Khan, Moazzam Rafiq; Roobab, Ume; Rajoka, Muhammad Shahid Riaz; Inam‐ur‐Raheem, Muhammad; Anwar, Raheel; Ahmed, Waqar; Jahan, Musarrat; Ijaz, Muhammad Rafaqat Ather; Asghar, Malik Muhammad; Shabbir, Muhammad Asim; Aadil, Rana Muhammad
Abstract: Fresh‐cut foods have become highly popular as these commodities are convenient to manage with premium freshness and quality. However, the shelf life of fresh‐cut potatoes is limited. The traditional practice consists of a set of operations including washing, peeling, slicing, chemical treatment, packing, and storage. Besides, various chemical or synthetic additives are being applied to tackle quality‐related issues such as browning, textural degradation, microbial spoilage, and shelf‐life stability. Nevertheless, the demand for natural additives and nonthermal preservation techniques has increased with growing concerns about the potential health risks of chemical additives. This review paper discusses the use of various synthetic and natural food additives alone or in combination with the emerging nonthermal technologies for enhancing the quality characteristics of fresh‐cut potatoes. Overall, the nonthermal processing technologies including sonication, cold plasma, high‐pressure processing, ultraviolet, and pulsed electric field would be promising treatments for the fresh‐cut food industry compared with conventional approaches. Practical applications: Fresh‐cut potato is highly susceptible to microbial spoilage and undergoes rapid loss of quality due to high moisture content and rapid metabolic rate. Researchers are exploring alternative nonthermal processing technologies for producing shelf‐stable food products using a clean label approach. This review covers some recent advances concerning the use of chemical compounds, including plant natural antimicrobials and antioxidants, as well as nonthermal technologies for the quality maintenance of fresh‐cut potato. These technologies are known to be safe, cost‐effective, and can be upscaled for use in existing processing lines of the food industry.